Mapping the Progress of Technological Pedagogical and Content Knowledge Research: Bibliometric Analysis - Prihantini, Prihantini; Rukmini, Ai; Mahardhani, Ardhana Januar; Mustika, Amalia (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This bibliometric analysis maps the progress of Technological Pedagogical Content Knowledge (TPACK) research over the past decade, highlighting its significance in integrating technology into education. Despite its growing relevance, existing literature indicates a concerning lack of collaboration across disciplines and minimal contributions from developing countries. The study employs bibliometric methods to analyze publication trends, identify key authors and institutions, and explore thematic relationships within TPACK research. Findings reveal a significant increase in TPACK publications, particularly peaking in 2022, with a diverse range of topics being addressed, including educational technology, teacher education, and the impact of COVID-19. The analysis also underscores the need for further interdisciplinary research and emphasizes the potential for TPACK to enhance educational practices, especially in the context of modern technological advancements. By providing insights into publication patterns and identifying under-researched areas, this study aims to guide future research efforts and promote a more comprehensive understanding of TPACK's applications in education.